Interspecific Variation in Wildlife Hazards to Aircraft: Implications for Airport Wildlife Management - DeVault, Travis L.; Belant, Jerrold L.; Blackwell, Bradley F.; Seamans, Thomas W. (DigitalCommons@University of Nebraska - Lincoln, 2011)
Understanding the relative hazards of wildlife to aircraft is important for developing effective management programs. We used Federal Aviation Administration National Wildlife Strike Database records from 1990 to 2009 in the United States to rank the relative hazard of wildlife to aircraft. We summarized data for 77 species or species groups with ≥20 records where collisions occurred ≥500 ft (152 m) above ground level. We also assessed the effects of avian body mass, body density, and group size on relative hazard scores. The 3 most hazardous species or species groups were mule deer (Odocoileus hemionus), white-tailed deer (O. virginianus), and domestic dogs. ‘‘Other geese’’ (snow goose [Chen caerulescens], brant [Branta bernicla], and greater white-fronted goose [Anser albifrons]) was the most hazardous bird group. Ten of the 15 most hazardous bird species or species groups are strongly associated with water. Avian body mass was strongly associated with percentage of all strikes that caused damage, but not for species exceeding median body mass (1,125 g) of birds in damaging strikes. In contrast, percentage of damaging strikes increased when multiple birds were involved, but only for those species with body mass ≥1,125 g. Managers should prioritize efforts that will reduce habitat suitability for those species most hazardous to aircraft. We recommend use of exclusion (e.g., fences) for managing large mammals and habitat modifications (e.g., reductions in standing water) accompanied by hazing for reducing bird use of airports. We also recommend that evaluations of jet turbine engine performance following bird ingestions consider using multiple birds with body mass >1,000 g.